Beclometasone inhaler-induced recovery of refractory peri-ileostomy skin complications. (23rd March 2023) - McDonald, Mary; Connelly, Tara M; Brett, Aishling; McCullough, Peter; Cooke, Fiachra; Neary, Peter
Abstract : Peristomal skin complications (PSCs) are relatively common in ostomy patients, particularly in those with ileostomies. Non-healing irritation presents a clinical challenge and leads to pain and impaired quality of life for patients. Methods: The cases of four ileostomy patients experiencing severe, challenging PSCs refractory to appliance changes, conventional dressings and barrier creams are discussed. Findings: The cases of one male and one female patient with an end ileostomy post-subtotal colectomy for ulcerative colitis, one female with a defunctioning ileostomy post-anterior resection for sigmoid carcinoma and one male with an end ileostomy with a complex Crohn's surgical history are described. Two puffs of a 250 mcg metered dose beclometasone inhaler were applied to the affected skin once or twice daily. Treatment ranged from 6 to 21 days. Complete resolution was seen in all cases. Conclusion: Topical use of a beclometasone inhaler was effective for severe peri-ileostomy PSC secondary to four different aetiologies. Further studies are warranted to determine the effectiveness of this treatment in a larger patient cohort.